International Standing Conference for the History of Education (ISCHE): Networks, internationalisation, and scientific communication - Hernández Huerta, José Luis; Payà Rico, Andrés (El Futuro del Pasado, 2022)
The objective of this study is to map the international networks of research, circulation, and scientific communication in the history of education, at a global level. In order to do so, we analyse the activity of the International Standing Conference for the History of Education (ISCHE). The focus is placed on the following: the make-up and organisation of the community of education historians; the arenas set up to encourage collaboration, debate and consensus in research in the field; collaboration among researchers, and the influence of transnational perspectives; avenues of research and areas of focus; and the communication channels by which ideas and findings are published and exchanged. The documentary sources used are the minutes of ISCHE annual congresses and general assemblies, alongside other research and previous studies. The main variables are: the language in which papers are published; the countries from which the authors come; international collaboration among authors; the historical period analysed; and the country or region being studied. After examining over 3600 contributions, we conclude that, globally, the international network in history of education is in good health, and there is an appetite for research with an international focus. However, there is room for improvement by promoting more extensive international collaboration among researchers, expanding the scope of research to take a supranational or even global view, and extending the study of the history of education to pre-modern times.